A Monthly Subscription to Gendered Sexuality - Kozicki, Bethany (My University, 2014)
The media has become a large part of our everyday lives. Lifestyle magazines, such as Cosmo and Men's Health, dictate to the readers a social construction of what is considered a normal sexual script for women and men. Using a qualitative content analysis, this study analyzes the differences in sex advice that is given to men and women within these magazines in order to understand how media reinforces gendered sexual scripts and influences perceptions of normality within relationships.
Color poster with text and images.
Keywords: Sexuality; Magazines; Heteronormativity; Gender norms; Posters